Road Damage Analysis Using PCI Method: Case Study of Babakan – Pabuaran Road Section Kab. Cirebon - Lestari, Rossy Indah; Sugiyanto, Martinus Agus (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2025)
Problematic road infrastructure or pavement due to heavy and repeated traffic volume will cause a decrease in road quality. One of the road damage problems occurred on the Babakan - Pabuaran road section, Cirebon Regency. In this case, the condition survey is carried out visually and then analyzed using the Pavement Condition Index (PCI) method. From the results of data on the condition of the Babakan - Pabuaran road of Cirebon Regency along 3 km and 5 m wide with bending pavement, it can be seen that the more dominant type of damage is the 83.37 m² Basin, 57.27 m² Grain Release, 31.15 m² Hole, 27.08 m² Slippery Aggregate, 21.33 m² Crocodile Skin Crack and 14.92 m² Amblas. The Pavement Condition Index (PCI) value of bending pavement on the Babakan – Pabuaran road section of Cirebon Regency is 41.53 of these figures in the condition of the road section in the Fair category. Based on PCI values, it shows that the percentage of handling road conditions obtained is good, no handling is needed by 14%, rehabilitation by 14%, maintenance by 26% and reconstruction by 46%.